Enhancement of the Mechanical and Thermal Properties of Polypropylene and Nylon 6.6 Composite Blends. (11th April 2023) - Al-Haik, Mohammad Yousef; Aldajah, Saud Hamad; Kabir, Mohammad Mazedul; Siddique, Waseem Ahmad; Haik, Yousef; Islam, Md Mainul
Abstract : The mechanical and thermal properties of nylon 6.6 on polypropylene (PP) blends were investigated. Five weight percentages of nylon 6.6, 1 wt%—5 wt%, were blended with PP by an injection molding process to produce PP/nylon 6.6 blends. The impact of the mixture on the mechanical properties was investigated by performing a three-point bend test to determine the flexural strength and hardness test using nanoindentation. Both differential scanning calorimetry and thermogravimetric analysis were used to study the thermal properties of the mixture. Chemical and morphological testing was performed by Fourier-transform infrared spectroscopy and scanning electron microscope tests. Mechanical testing revealed improved strength, modulus, and hardness of the PP/nylon 6.6 blends. The 2 wt% blend showed elastic modulus, tensile, and yield stress enhancement. TGA showed variable results with improved thermal resistance for the 3 wt% and 4 wt% blends, whereas there was no effect for the 2 wt% blend and reduced thermal resistance for the 1 wt% and 5 wt% blends. DSC analysis revealed no influence on the melting temperature of the blends. SEM images showed a homogeneous mixture between PP and nylon 6.6, which substantiated the interfacial adhesion between PP and nylon 6.6 and was verified by FTIR.